SOCIAL MEDIA RECRUITMENT: IN JOB FINDINGS AMONG THE GENERATION Y (FRESH GRADUATES) - Lingkeswari A/P Kunasagaram; Christina Rathy A/P Anthony Samy, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The social media phenomenon has opened new paths of engagement and revolutionized the exchange of information. With more people engaging with social media, it is worth investigating its relevance to the recruitment process. The purpose of this paper is to assess how employers can make the best use of social media as part of the recruitment process. It examines which platforms effective suited to hosting job search information, which can help achieve recruitment goals and how candidates are used social media recruitment as a job finding tool. As the research examines a number of key questions on the current new ways of recruiting and its effectiveness, advantages such as accessibility and its impact on management. It analyzes the relationship between social media and recruitment and its impacts. There has been a relative research recommendation on exploring the processes and procedures individuals and employee organizations utilize with respect to employing social media in the workplace in the future, and specifically within the recruitment process. The findings confirm a dual-use of social media by employers, connected with a belief that strengthened connections with potential applicants are possible, alongside the original intended use as an attraction tool. It has also resulted in this research a significant positive relationship among social media recruitment as first would be Facebook is efficient and effective. This research concludes by highlighting a need for further research and recommendations for HRM practice.